Implementation Of Murabaha Financing In Baitul Maal Wat Tamwil: A SWOT Analysis - Assodiqoh, Nur Ma'rifah; Fitriyani, Yeny; Yanuar, Fuad; Purwanto, Purwanto; Pambudi, Fajar (LPPM ISNJ Bengkalis, 2024)
This research uses the SWOT approach to review Murabaha financing at Baitul Maal Wat Tamwil (BMT). This research is field research, with primary and secondary data sources, such as questionnaires, interviews, and literature. The research sample consisted of 20 people and three informants. Data analysis uses a mixed method approach, quantitatively and qualitatively, with the IFAS, EFAS and SWOT matrices. The research results found that several internal and external factors need to be evaluated, such as public trust, quality leadership, networks and partnerships, excellent and friendly service, practical procedures, and strategic location, which are assets that organizations can utilize to socialize Murabaha financing in the community. Meanwhile, external opportunities such as support from government agencies, a majority Muslim community, and local marketing strategies offer further growth and development potential. However, there are areas for improvement in education and awareness, product and service innovation, limited resources, and local marketing strategies that need to be overcome. Furthermore, threats from many competitors, the same target market, and a low public understanding of Islamic financing exist. This research can be helpful as a reference for future research and then become a reference for BMT in aligning organizational strategy with internal strengths and external opportunities, as well as overcoming existing weaknesses and threats.